Role of adenosine pathway on cell growth and stress response in Drosophila - Maaroufi, Houda Ouns (Jihočeská univerzita, 2022)
The thesis surveyed the effects of the adenosine pathway on cell growth and stress response. We described the effects of mutation of the concentrative nucleoside transporter cnt1 on male fertility, particularly spermatogenesis, using a Drosophila melanogaster model. We also described the effects of the adenosine pathway on the cytotoxicity of mHTT.
Role of adenosine pathway on cell growth and stress response in Drosophila
Keywords: cell growth; stress response; cnt1; adenosine pathway; metabolism; mHTT; cell growth; stress response; cnt1; adenosine pathway; metabolism; mHTT